P-134 Patient-centred quality improvement in palliative and end of life care: learning from online feedback. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Russell, Sarah; Alexander, Gina; Munro, James
Abstract : Background: Patient and family feedback is fundamental to care as it provides information about the quality of care experiences and involves patients and the public. Feedback methods vary e.g., face to face conversations, questionnaires, touch screens etc. However, near real-time, online feedback about care and services is under developed in palliative and end of life care (PEOLC). We report upon a 'work in progress' quality improvement project using an online platform which enables patients/families to feedback recent PEOLC experiences, leading to learning and change in the organisation. Experience with online feedback suggests that both patients and staff feel that clinical teams should be directly involved in responding online. Aim(s): The aims over two years are to: 1. Test the value and effectiveness of near real-time online feedback in 10 UK-wide PEOLC hospital, hospice or community teams 2. Teach and support the teams how to use the online platform and use feedback for learning, service development, change and demonstrate patient-led outcomes. Methods(s): May 2017 to Sept 2019; 10 PEOLC clinical teams (up to 20 people per team) are being educated and supported in using online feedback in their service. This includes creating email alerts, responding, reporting, and data visualisations. The programme offers a 'community of practice' (CoP) approach to supporting staff in learning to use feedback for quality improvement and wider cultural change. Results: A mixed method evaluation using qualitative (to understand the experience) and quantitative (to measure the activity) data, from patient, team and organisation perspectives, including: online platform data, experiences, outcome measurements, staff confidence, patient/family views, QI activity, CoP interaction and turning learning into care. Conclusion: Over two years the project will provide an ongoing understanding of the challenges, opportunities and outcomes in using near-real time feedback via an online platform in PEOLC. With recommendations for implementing in other PEOLC settings.